Comparison of Commercial and Palm Slag Motorcycle Brake Pads Performance - Badri, Muftil; Arief, Dodi Sofyan; Prayitno, Adhy (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
This paper presents a number of experimental data and techniques used in performance of commercial and palm slag motorcycle brake pads. The experiments include wear and hardness tests. The wear behavior of motorcycle brake pad that was observed in the study on sliding contact member brake discs results in the conversion of kinetic energy into heat at the pad and disc interface leads to this investigation. The effects of speed of disc brake rotor are presented. Experimental results of the respective tests are presented on two motorcycle brake pads, namely commercial brake pad (CBP) and palm slag brake pad (PBP). It was found that the wear behavior of palm slag brake pad is influenced by design of geometry shape of motorcycle brake pad. The wear behavior of CBP and PBP composite depend on wet and dry condition. It is clearly seen that wear behavior of PBP composite increase significantly with dry condition. Wear behavior increase significantly with the increase of rotor speed. With increasing speed of rotor disc, the hardness of PBP composite changes from low hardness to a more stable hardness behavior.